Monitoring telehealth vomiting calls as a potential public health early warning system for seasonal norovirus activity in Ontario, Canada. (2019) - Hughes, S. L.; Morbey, R. A.; Elliot, A. J.; McEwen, S. A.; Greer, A. L.; Young, I.; Papadopoulos, A.
Abstract : Norovirus is a predominant cause of infectious gastroenteritis in countries worldwide [1–5]. It accounts for approximately 50% of acute gastroenteritis (AGE) and >90% of viral gastroenteritis outbreaks [6, 7]. The incubation period ranges between 10 and 48 h and illness duration is generally 1–3 days with self-limiting symptoms; however, this duration is often longer (e.g. 4–6 days) in vulnerable populations such as hospital patients or young children [2, 8]. Symptomatic infection of norovirus presents as acute vomiting, diarrhoea, abdominal cramps and nausea, with severe vomiting and diarrhoea (non-bloody) being most common [2, 5, 9].